The effect of accounting ratios on firm's value: Evidence from Malaysian listed companies - Baba, Bello Usman (2014)
This study empirically examines the effect of accounting ratios on firms' value among Malaysian listed companies. The study utilized a sample of top 100 leading companies in Malaysia (Index Companies) for the period covering 2008-2012. Based on the extensive review of literature, conceptual framework was proposed and hypotheses were developed to examine the relationship between the variables of the study. A multiple regression analysis was used in analyzing the data collected. Findings from the study revealed that both liquidity and profitability ratios have a significant effect on firms' value. On the basis of the findings, the study concludes that there is increasing need for a more credible and comprehensive disclosure of accounting ratios in the annual reports of companies. On this ground, the study recommends that Malaysian regulatory authorities implement a policy or a guideline that will encourage a uniform and comprehensive disclosure of accounting ratios by companies. This in turn will avail investors and other users of financial information a better means of evaluating and making a qualitative judgment on companies' financial performance